Development of the Moral Disengagement from Refugees Scale: A Psychometric Analysis - AKINCI, TUNCAY (My University, 2023)
This study aims to develop a tool that can measure the level of individuals’ moral disengagement from asylum seekers. The study develops the Moral Disengagement from Refugees Scale for this purpose by taking into account the steps for scale development. To do this, the study collected data at three different times for three different purposes (exploratory factor analysis [EFA; n = 342], confirmatory factor analysis [CFA; n = 209], and criterion validity [n = 79]). During the formation of the study group, the participants were informed about the purpose of the study, with sensitivity being shown toward voluntary participation. According to the results from the EFA conducted after obtaining the data, the scale consists of five factors and 28 items, with these five factors explaining 64.251% of the variance. Cronbach’s alpha of reliability for the overall scale was found to be 0.943, with the results for each subscale being within acceptable values. As a result of the CFA, the scale’s subdimensions and items were confirmed, and the goodness-of-fit values are seen to fall within the appropriate reference ranges (χ2 / df= 1.682; RMSEA = 0.066; SRMR = 0.010; IFI = 0.953; CFI = 0.952; GFI = 0.890). The findings obtained as a result of the research reveal the Moral Disengagement from Refugees Scale to be able to be used as a sufficiently valid and reliable measurement tool.
Keywords: Moral Disengagement; Asylum Seeker; Scale Development; Validity; Reliability